Can biomarkers help us to understand the pathogenesis of coronary slow flow? Endocan and omentin-I in slow coronary flow phenomenon - Serhat Sığırcı; Remzi Sarıkaya; Kudret Keskin; Süleyman Sezai Yıldız; Saadet Pilten Güzel; Gökhan Çetinkal; İmran Önur; Kadriye Orta Kılıçkesmez (KARE Publishing, 2019)
Objective: The pathophysiology of the slow coronary flow (SCF) phenomenon is still unclear. The two most frequently cited mechanisms of SCF are endothelial dysfunction and subclinical diffuse atherosclerosis. The aim of this study was to investigate the relation of SCF to serum endocan levels which is associated with endothelial dysfunction and to serum omentin-I levels which is associated with atherosclerosis. Methods: A total of 42 patients with SCF and 43 controls with normal coronary flow based on a coronary angiogram were enrolled. Serum endocan and omentin-I levels were measured and the presence of SCF was determined according to Thrombolysis in Myocardial Infarction frame count (TFC) calculations. Results: The omentin-I level was significantly lower and the endocan level was significantly higher in patients with SCF than in the controls. Receiver operating characteristic curve analysis revealed that the sensitivity and specificity of endocan for SCF was 66% and 70%, respectively (area under the curve [AUC]: 0.760, 95% confidence interval [CI]: 0.65-0.86; p<0.001), and the comparable values for omentin were 66% and 61% (AUC: 0.630, 95% CI: 0.51-0.75; p=0.049). Multivariate logistic regression analysis revealed that a high endocan level (odds ratio [OR]: 6.8, 95% CI: 1.849-2.439, cutoff: 2.45 ng/mL; p=0.003) and a low omentin-I level (OR: 3.6, 95% CI: 1.057-12.893, cutoff: 4.63 ng/mL; p=0.041) were independently associated with the presence of SCF. In patients with SCF, the endocan level was positively correlated with the mean TFC, while the omentin-I level was negatively correlated (r=0.44; p<0.001 and r=-0.22; p=0.049, respectively). Conclusion: These results revealed that endocan and omentin-I might be useful biomarkers for predicting the presence and severity of SCF.